Molekulární diferenciace pohlavních chromosomů předivek rodu Yponomeuta - Veselá, Jana (Jihočeská univerzita, 2012)
Structure of the karyotype of three species in ermine moths (Yponomeuta: Yponomeutidae, Lepidoptera) was investigated by means of several cytogenetic methods (DAPI staining, orcein staining, CGH and GISH with telomeric probe) focusing on their sex chromosomes. Additionally, the origin of the Z2 chromosome in the WZ1Z2/Z1Z1Z2Z2 sex chromosome system (specific for this family of butterflies) was tested using southern hybridization.
Molecular differentiation of sex chromosomes in ermine moths of genus Yponomeuta
Keywords: karyotyp; barvení DAPI; barvení orceinem; CGH; GISH s telomerickou sondou; Southernova hybridizace; Yponomeuta; karyotyp; DAPI staining; orcein staining; CGH; GISH with telomeric probe; southern hybridization; Yponomeuta